Maximal Estimates of Schrödinger Equations on Rearrangement Invariant Sobolev Spaces. (2nd January 2019) - Ho, Kwok-Pun
Abstract: We establish the maximal estimates for the solutions of some initial value problems on rearrangement-invariant quasi-Banach function spaces. Our result covers the cases for which the initial value problem is given by the Schrödinger equation.